2022
DOI: 10.1055/s-0042-1759621
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Antibiotic-Resistant Bacteria in Libya Based on Different Source of Infections

Abstract: In recent years and for decades, antimicrobial resistance (AMR) has expanded into a major clinical issue. Infections were no longer a life-threatening issue for clinicians after the discovery of antibiotics. The misuse or overuse of antibiotics, however, contributes to global AMR, and numerous mobile genetic elements and relevant resistant genes worsen the spread of resistance. As antibiotics lose their effectiveness, a growing number of infections such as pneumonia, tuberculosis, and gonorrhea are getting har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…6 Animal studies included evaluation of the protective effects of doxycycline against vanadium-induced hepatoxicity in rats, 7 and central nervous system effects of the methanolic extract of the leaves of Capparis spinosa L. 8 A clinicopathological characteristics of prostate lesions in surgical specimens of Libyan patients were prescribed in a retrospective study, 9 and a review article provided information on the current state of antimicrobial resistance in Libya. 10 Another original research article reported the magnitude of burnout among physicians in Benghazi-Libya, 11 and a letter to the editor describing the 8th Libyan Cardiac Society Congress Recommendations. 12…”
mentioning
confidence: 99%
“…6 Animal studies included evaluation of the protective effects of doxycycline against vanadium-induced hepatoxicity in rats, 7 and central nervous system effects of the methanolic extract of the leaves of Capparis spinosa L. 8 A clinicopathological characteristics of prostate lesions in surgical specimens of Libyan patients were prescribed in a retrospective study, 9 and a review article provided information on the current state of antimicrobial resistance in Libya. 10 Another original research article reported the magnitude of burnout among physicians in Benghazi-Libya, 11 and a letter to the editor describing the 8th Libyan Cardiac Society Congress Recommendations. 12…”
mentioning
confidence: 99%
“…6 Animal studies included evaluation of the protective effects of doxycycline against vanadiuminduced hepatoxicity in rats, 7 and central nervous system effects of the methanolic extract of the leaves of Capparis spinosa L. 8 A clinicopathological characteristics of prostate lesions in surgical specimens of Libyan patients were prescribed in a retrospective study, 9 and a review article provided information on the current state of antimicrobial resistance in Libya. 10 Another original research article reported the magnitude of burnout among physicians in Benghazi-Libya, 11 and a letter to the editor describing the 8th Libyan Cardiac Society Congress Recommendations. 12 Publication in LIMUJ is still free, charging no processing or publication fees.…”
mentioning
confidence: 99%